Radioprotective strategies for interventional echocardiographers during structural heart interventions. Issue 2 (9th September 2018) - Corrigan, Frank E.; Hall, Michael J.; Iturbe, Jose Miguel; Condado, Jose F.; Kamioka, Norihiko; Howell, Sharon; Thourani, Vinod H.; Clements, Stephen D.; Babaliaros, Vasilis C.; Lerakis, Stamatios
Abstract: Objective: We investigated radioprotective strategies for the interventional echocardiographer (IE) during structural heart interventions in comparison with the interventional cardiologist (IC). Background: Structural heart interventions are expanding in complexity with increased reliance on IE. Recent reports have demonstrated concerning exposure and higher radiation to the IE. Methods: We monitored 32 structural interventions — 19 transcatheter aortic valve replacements (TAVR), 6 transcatheter mitral valve repairs, 5 paravalvular leak closures, and 2 atrial septal defect closures. Seventeen utilized transesophageal echocardiography (TEE) while 15 used transthoracic echocardiography (TTE). Members of the IC and IE teams wore multiple dosimeters on different sites of the body to measure radiation dose to the total body, lens of the eye, and hand. During each case, IE utilized dedicated radiation shielding. Results: Mean doses were higher for the primary IC than the primary IE: IC#1–99, 222, 378; IE#1–48, 52, 416 (body, lens, and hand doses in μSv). IE radioprotective strategies were able to reduce body and lens doses compared to IC during both TTE and TEE‐guided procedures. Hand equivalent dose remained higher for the IE driven by exposure during TEE‐guided procedures (IC#1 294 vs. IE#1 676 μSv). In a subgroup using radioprotective drapes during TTE‐guided TAVR, IC dose was reduced without effect on the IE. Conclusions: Radiation exposure during structural heart interventions is concerning. With dedicated shielding, IE received lower doses to the body and lens than IC. Further optimization of structural suite design and shielding is needed.